Performance of Tourism Sector With Regard to the Global Crisis - A Comparative Study Between Indonesia, Malaysia and Singapore - Purwomarwanto, Yunitazari Laksmi (2014)
Tourism contribute to the growth of economy of a nation through employment, multiplier effect, foreign exchange earnings and also contribute to positive balance of payments. Therefore developed and developing countries has incorporated tourism into their long-term economic development planning. However, tourism is vulnerable to crisis events, such as natural disasters, outbreaks, political turmoil and also financial crisis. This study examines the tourism sector performance of Indonesia, Malaysia and Singapore with regards to the recent global crisis. The three countries are chosen because they are closely related in terms of proximity and also in regional cooperation; however they are different in terms of the size of economy and openness. This study employs ordinary least square method to investigate the significance of tourism to economic growth. Comparative study also done in the discussion in order to analyze how the respective countries differ in tourism performance. Number of tourist arrival and hotel's rate of occupancy are employed as proxy to represent tourism growth. The study finds out that for the three countries, tourism is significance for the economic growth. Tourism also affected by financial crisis, as seen from the short dip that experienced by number tourist arrival and hotel's rate of occupancy in first quarter of 2009. Nevertheless, it is considered as a resilient sector as it is already recovered in 2010. Based on comparison, Singapore is worse affected compare to the other two. It may be link to strong real effective exchange rate, which makes the price less competitive compare to the other two. This study also finds that regional tourists actually plays huge role in the development of tourism , because they hold the largest portion of tourist arrivals compare to outside-regional tourists. Moreover, the number of regional tourist has been stable despite of financial crisis occurred.